Corporate rescue as sustainable mechanism for strengthening companies in Nigeria? (2022)
Company, upon its incorporation becomes a legal personality or “legal abstraction” with powers to act for it with respect to formation of contract, right to sue and be sued (a juristic personality), right to own properties (real properties and chattels) among others. However, the characteristic that distinguishes companies from other forms of business organization is that aside from the companies being different from its members, it has the capacity for perpetual existence. The exit of its members will not necessarily ‘terminates’ the life of the company, since at best such member reserves the right of transfer his/her shares. This legal attribute of a company has however not been true of many companies that found themselves in the “murky waters” of bankruptcy and may therefore have to go through the winding up process, which usually ultimately “terminates” the life of such companies. However, with the dwindling fortunes of companies in the 21st century, and many having to wind up’ business activities as a result of insolvency, it becomes imperative that attempts be made to rescue the company from ‘dying’ rather than wait to give same ‘decent burial’ by way of liquidation and winding up process. This new concept is referred to as “Corporate Rescue”